Climate-smart investments in the African Agrifood Sector: Risk and impact assessment of eight agrifood businesses in Sub-Saharan Africa - Masika, Daniel; Mufti, Samaa; Derenoncourt, Marie Ena; Burra, Dharani Dhar; Cosgrove, Bethany Emma; Costa Jr, Ciniro; Newman, Richard; Grosjean, Godefroy; Vishnumolakala, Harsha; Falconer, Angela; Chin, Wen E (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This info note describes the methodology and findings of the risk and Climate Smart Agriculture impact assessment conducted for eight agrifood businesses in Sub-Saharan Africa as part of the CLIC Agrifood Investment Connector.